Kajian Desain Jalan Tambang Pengangkutan Batubara dari Pit Menuju Stockpile - Rahma Wita; Zaenal; Indra Karna Wijaksana (Jurnal Riset Teknik Pertambangan, 2024)
Abstract. PT Era Perkasa Mining Site Peranap is a coal mining company operating in Katipo Village, Peranap District, Indragiri Hulu Regency, Riau Province, with an IUP covering 1,350 hectares. The site is located 232 km from Sultan Syarif Kasim II International Airport, an estimated 6-hour drive by land. The main issue at this site is the failure to meet the transportation production target of 200,000 BCM per month, due to non-standard road geometry and high ground pressure in some segments. The study was conducted through direct field observation to assess the site conditions. Data collected included road width, road gradient, ground pressure, cycle time, and production calculations. The results showed that the road geometry was 16 meters wide in segment R-S and the minimum road width was 4 meters. The road gradient in segment C-D was 13%, and the ground pressure was 334.55 lbs/inch². The transportation production was 181,540 BCM per month, below the target. Improvements were made by adjusting the road width and gradient to meet standards (Kepmen ESDM No.1827K/30/MEM/2018) and AASHTO, and adding hardening materials to reduce ground pressure. After these efforts, transportation production increased to 232,440 BCM per month, meeting the target. Abstrak. PT Era Perkasa Mining Site Peranap adalah perusahaan tambang batubara yang beroperasi di Desa Katipo, Kecamatan Peranap, Kabupaten Indragiri Hulu, Provinsi Riau, dengan IUP seluas 1.350 hektar. Lokasi ini berjarak 232 km dari Bandara Internasional Sultan Syarif Kasim II, dengan estimasi perjalanan darat selama 6 jam. Permasalahan di lokasi ini adalah target produksi pengangkutan yang belum tercapai sebesar 200.000 BCM per bulan, disebabkan oleh geometri jalan yang tidak sesuai standar dan ground pressure yang besar di beberapa segmen. Penelitian dilakukan dengan pengamatan langsung di lapangan untuk mengkaji kondisi lokasi. Data yang diambil meliputi lebar jalan, kemiringan jalan, ground pressure, cycle time, dan perhitungan produksi. Hasil perhitungan menunjukkan geometri jalan 16 meter pada segmen R-S dan lebar jalan minimum 4 meter. Kemiringan jalan di segmen C-D memiliki grade 13%, dan ground pressure sebesar 334,55 lbs/inch². Produksi pengangkutan hanya mencapai 181.540 BCM per bulan, sehingga target belum tercapai. Upaya perbaikan dilakukan dengan menyesuaikan lebar dan kemiringan jalan sesuai standar (Kepmen ESDM No.1827K/30/MEM/2018) dan AASHTO, serta menambah material pengeras untuk mengurangi ground pressure. Setelah upaya ini, produksi pengangkutan meningkat menjadi 232.440 BCM per bulan, sehingga target tercapai.